PERAN KREDIBILITAS INFLUENCER SARAH AYU DAN CONTENT QUALITY TERHADAP ONLINE ENGAGEMENT DAN PURCHASE INTENTION PADA MEDIA SOSIAL INSTAGRAM - Putri, Annisa Fadilla Purnomo; Rimadias, Santi (Journal of Accounting, Management and Islamic Economics, 2024)
This research explores the role of beauty influencer Sarah Ayu's credibility on online engagement, the influence of online engagement on purchase intention, and the influence of content quality on the purchase intention of Instagram users in Indonesia. Data was collected through a Google Forms questionnaire filled out by 110 active Instagram users and analyzed using SmartPLS 3.0 software. The findings are: 1) Influencer Credibility significantly increases online engagement. 2) Online engagement has no significant effect on Purchase Intention. 3) Content Quality significantly increases Purchase Intention. These insights provide valuable guidance for marketers and companies looking to leverage influencer credibility, online engagement, and content quality to drive purchase intent among Instagram users in Indonesia.